Pengurangan Risiko Bencana: Korelasi Pengetahuan dan Kesiapsiagaan Siswa Sekolah Menengah Atas di Kota Batu - Syaifulloh, Mochammad; Soekamto, Hadi; Wagistina, Satti; Utomo, Dwiyono Hari (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
Internalization of disaster risk reduction (DRR) education in the school curriculum has been applied to various levels of education in Indonesia. Given that disaster knowledge is closely related to preparedness, the relevance of both becomes something essential to study. This study aims to 1) describe the level of knowledge of high school students regarding DRR and their preparedness to face disasters, 2) explore the relationship between DRR knowledge and student preparedness to face disasters. This research is a descriptive correlative study. This research was conducted in Batu City which has a status of a multi-disaster prone area. The data collection was done by survey. The number of research samples were 240 students spread across SMAN 1 Kota Batu, SMAN 2 Kota Batu, SMAN 3 Kota Batu, and SMA Islam Kota Batu. The research data was analyzed using Spearman's nonparametric test with a significance of 0.01. The results of the study showed that the student's DRR knowledge level belonged to the category of